Exploring Asset Pricing Models and Market Efficiency - Tompo, Junaedi (Yayasan Pendidikan Bukhari Dwi Muslim, 2023)
The study aims to critique traditional asset pricing models like the Capital Asset Pricing Model (CAPM), highlighting their limitations in capturing the complexities of real-world financial markets. Through meticulous literature review and empirical analysis, it emphasizes the need for more sophisticated frameworks accommodating multifaceted risk and return dynamics. The research unveils significant variations in market efficiency across different conditions and asset classes, underscoring critical determinants such as information dissemination and investor behavior. Moreover, it advocates for integrating insights from behavioral finance into asset pricing models to enhance their robustness. The implications extend to investors, policymakers, and academics, emphasizing the importance of informed decision-making and ongoing research to navigate modern financial markets effectively.